Delia Grace on dealing with food safety, nutrition, and public health crises - Grace, Delia (International Food Policy Research Institute, 2014)
Parallel Sessions 3: Dealing with Shocks. Delia Grace, Program Leader, Food Safety and Zoonoses, Integrated Sciences, International Livestock Research Institute (ILRI), Kenya, panelist at Parallel Session 3F on "Health Shocks: Dealing with Food Safety, Nutrition, and Public Health Crises." IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info